Genome-Wide Association Study of Topsoil Root System Architecture in Field-Grown Soybean [Glycine max (L.) Merr.] - Dhanapal, Arun Prabhu; York, Larry M.; Hames, Kasey A.; Fritschi, Felix B. (Frontiers in Plant Science, 2021)
Water and nutrient acquisition are critical functions of plant root systems. Root system architecture (RSA) traits are often complex and controlled by many genes. This study is the first genome-wide association study in soybean that reports genetic loci for a broad set of RSA traits. A collection of 289 soybean genotypes was grown in three environments, root crowns were excavated and 12 RSA traits assessed. The first two components of a principal component analysis of these 12 traits were used as additional aggregate traits for a total of 14 traits. Marker-trait association for RSA traits were identified using 31,807 single nucleotide polymorphisms (SNPs) by genome-wide association analysis. In total, 283 (non-unique) SNPs were significantly associated with one or more of the 14 root traits. Of these, 246 were unique SNPs and 215 SNPs were associated with a single root trait, while 26, four and one SNPs were associated with two, three and four root traits, respectively. The 246 SNPs marked 67 loci associated with at least one of the 14 root traits. Seventeen loci on 13 chromosomes were identified by SNPs associated with more than one root trait. Several genes with annotation related to processes that could affect root architecture were identified near these 67 loci. Additional follow-up studies will be needed to confirm the markers and candidate genes identified for RSA traits, and to examine the importance of the different root characteristics for soybean productivity under a range of soil and environmental conditions.